Use of the Internet and its Impact on Productivity and Sales Growth in Female-Owned Firms: Evidence from India - Aparna Gosavi (Journal of Entrepreneurship, Management and Innovation, 2017)

(untitled)
The Internet has completely transformed our lives on an individual basis in many ways, ranging from the way we communicate through the way we socialize to the way we shop and travel. Businesses are no excepton to this premise. This paper studies the adopton of the Internet by female-owned frms in India. It uses the World Bank’s Enterprise Surveys Program data set for the year 2014 to study the adopton of the Internet by more than 10,000 frms in the country. Afer controlling for a large number of frm-level characteristcs, empirical results obtained indicate that femaleowned frms are more likely to use the Internet than their male counterparts. However, further empirical analysis shows that more intensive adopton of the Internet by these female-owned frms does not necessarily translate into beter performance. Specifcally, the adopton of the Internet does not make female-owned frms more or less likely to have beter productvity and sales growth in contrast to that of their male counterparts.